Long-term oncological outcomes in robotic versus laparoscopic approach for rectal cancer: A systematic review and meta-analysis. (August 2020) - Qiu, Hua; Yu, Dongjun; Ye, Shanping; Shan, Renfeng; Ai, Junhua; Shi, Jun
Abstract: Background: Short-term outcomes of robotic mesorectal excision for rectal cancer resection seem comparable to those of conventional laparoscopic mesorectal excision. However, the long-term oncological outcomes of robot mesorectal excision require further investigation. Materials and methods: The PubMed, EMBASE, Medline, and Cochrane Library databases were searched from the date of database inception to March 31, 2019 for all available trials; the results of robotic and laparoscopic mesorectal excision for rectal cancer surgery were compared. Survival parameters, including overall survival (OS) and disease-free survival (DFS), were independently extracted by two investigators. Hazard ratios (HRs) were calculated using random- or fixed-effects models. The presence of heterogeneity was assessed using Q test, and the extent of heterogeneity was quantified by I 2 index. The meta-analysis was performed using Review Manager software, version 5.3. Results: A total of seven studies including 2593 patients (1362 treated by robotic mesorectal excision and 1231 by laparoscopic mesorectal excision) were included. Pooled analyses showed no significant difference in OS (HR = 0.94, 95% confidence interval [CI]: 0.63 to 1.39, P = 0.75) or DFS (HR = 0.93, 95% CI: 0.79 to 1.10, P = 0.85) between the robotic and laparoscopic mesorectal excision for treatment of rectal cancer. Conclusion: Regarding long-term survival, robotic mesorectal excision for rectal cancer is comparable to laparoscopic mesorectal excision. More prospective, multicenter randomized trials with longer follow-up periods are needed to determine the long-term outcomes of patients undergoing robotic mesorectal excision. Highlights: Robotic approach has been reported to be safe yielded comparable short-term outcomes compared with laparoscopic approach. However, the long-term oncological outcomes have only been reported in cohort studies and the conclusions are inconsistent. No meta-analysis has been performed to analyze the long-term oncological outcomes of robotic approach for rectal cancer. This study was analyzed the Consolidated Standards of Reporting Trials guidelines.